2011
DOI: 10.1007/s10459-011-9278-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of surgeon empathy and emotional intelligence on patient satisfaction

Abstract: We investigated the associations of surgeons' emotional intelligence and surgeons' empathy with patient-surgeon relationships, patient perceptions of their health, and patient satisfaction before and after surgical procedures. We used multi-source approaches to survey 50 surgeons and their 549 outpatients during initial and follow-up visits. Surgeons' emotional intelligence had a positive effect (r = .45; p < .001) on patient-rated patient-surgeon relationships. Patient-surgeon relationships had a positive imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 22 publications
2
82
0
5
Order By: Relevance
“…Trust dimension scores showed positive correlation with age and satisfaction with the physician ( P < 0.01). These patterns are similar to those of established empathy and trust measurement tools …”
Section: Resultssupporting
confidence: 79%
“…Trust dimension scores showed positive correlation with age and satisfaction with the physician ( P < 0.01). These patterns are similar to those of established empathy and trust measurement tools …”
Section: Resultssupporting
confidence: 79%
“…Some researchers have argued that the incorporation of empathy in medical setting will dissuade physicians from having a dispassionate view of patients, therefore interfering with objective scientific decision-making (Bridget & Wohlers, 2010). Such skepticism is unwarranted, as a large body of literature shows that positive clinical outcomes are associated with the quality of the doctor–patient relationship and doctor–patient communication, and that empathy enhances both (Blatt, LeLacheur, Galinsky, Simmens, & Greenberg, 2010; Verheul, Sanders, & Bensing, 2010; Weng et al, 2011). On the other hand, doctors who reported a loss of empathy subsequently showed an increased rate of major medical errors (West et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Both awareness of the importance of patient-centred care and interest in the communication styles between doctors and patients are rising. Previous studies have shown that patient-centred attitude and good communication strengthen the doctor-patient relationship in dealing with illnesses, which in turn leads to better healthcare, patient satisfaction, patient adherence to treatment, and clinical outcomes [2,3,4,5,6,7]. Such results imply the need and appropriateness of changes in medical education.…”
Section: Introductionmentioning
confidence: 99%